Natural Disaster Hotspots: A Global Risk Analysis - Dilley, Maxx; Chen, Robert S.; Deichmann, Uwe; Lerner-Lam, Arthur L.; Arnold, Margaret (Washington, DC: World Bank, 2012)
Earthquakes, floods, drought, and other natural hazards cause tens of thousands of deaths, hundreds of thousands of injuries, and billions of dollars in economic losses each year around the world. Many billions of dollars in humanitarian assistance, emergency loans, and development aid are expended annually. Yet efforts to reduce the risks of natural hazards remain largely uncoordinated across different hazard types and do not necessarily focus on areas at highest risk of disaster. Natural Disaster Hotspots presents a global view of major natural disaster risk hotspots - areas at relatively high risk of loss from one or more natural hazards. It summarizes the results of an interdisciplinary analysis of the location and characteristics of hotspots for six natural hazards - earthquakes, volcanoes, landslides, floods, drought, and cyclones. Data on these hazards are combined with state-of-the-art data on the sub-national distribution of population and economic output and past disaster losses to identify areas at relatively high risk from one or more hazards.